First‐principles study of the surface phase diagrams of GaN(0001) and (000−1) under oxide vapor phase epitaxy growth conditions. Issue 8 (1st March 2017) - Kawamura, Takahiro; Kitamoto, Akira; Imade, Mamoru; Yoshimura, Masashi; Mori, Yusuke; Morikawa, Yoshitada; Kangawa, Yoshihiro; Kakimoto, Koichi
Abstract : First‐principles calculations are used to investigate the stable structures of the GaN(0001) and (000–1) surfaces under oxide vapor phase epitaxy growth conditions. The surface phase diagrams as a function of temperature and Ga pressure are described. It was found that the GaN(0001) surface is covered by OH groups. For the GaN(000–1) surface, the stable surface structure is with H atoms adsorbed on the topmost N atoms or an O atom stably incorporated into the Ga monolayer. We discuss the relationship between the growth conditions and O impurity incorporation. From the results, we suggest that high H2 pressure and high temperature growth conditions are favorable for decreasing O impurity incorporation.